Design and Implementation of Standard Operating Procedures (SOP) for Kacang “Disco” Production in Small-Scale Food Industry of Makassar, Indonesia - Muliani Muliani; Anwar Lubis (Universitas Negeri Semarang, 2025)
This study aimed to design and implement a Standard Operating Procedure (SOP) to improve the production process of Kacang Disco, a traditional coated peanut snack produced by small-scale food enterprises in Makassar, Indonesia. The absence of process standardization has led to inconsistent product quality and low production efficiency among micro and small enterprises. A participatory field-based approach was employed, involving observation, focus group discussions, SOP drafting, validation, and pilot testing in an active production setting. The finalized SOP standardized eight critical stages of production, including raw material preparation, mixing, coating, frying, draining, cooling, sorting, and packaging, with defined parameters for temperature, time, and hygiene control. Implementation of the SOP resulted in measurable improvements in product uniformity, color, and texture, supported by sensory evaluation results showing higher panelist scores for appearance, texture, and taste. The new process also enhanced production efficiency by reducing oil use and material waste. Supporting factors included easy access to raw materials and simple technology, whereas limited worker skills and lack of continuous training were the main constraints. The findings confirm that structured process documentation enhances quality assurance and productivity in traditional food manufacturing and can serve as a replicable model for small-scale food industries seeking sustainable process improvement